Novel animal defenses against predation: a snail egg neurotoxin combining lectin and pore-forming chains that resembles plant defense and bacteria attack toxins. - Marcos Sebastián Dreon (Public Library of Science (PLoS), 2013)
Although most eggs are intensely predated, the aerial egg clutches from the aquatic snail Pomacea canaliculata have only one reported predator due to unparalleled biochemical defenses. These include two storage-proteins: ovorubin that provides a conspicuous (presumably warning) coloration and has antinutritive and antidigestive properties, and PcPV2 a neurotoxin with lethal effect on rodents. We sequenced PcPV2 and studied whether it was able to withstand the gastrointestinal environment and reach circulation of a potential predator. Capacity to resist digestion was assayed using small-angle X-ray scattering (SAXS), fluorescence spectroscopy and simulated gastrointestinal proteolysis. PcPV2 oligomer is antinutritive, withstanding proteinase digestion and displaying structural stability between pH 4.0-10.0. cDNA sequencing and protein domain search showed that its two subunits share homology with membrane attack complex/perforin (MACPF)-like toxins and tachylectin-like lectins, a previously unknown structure that resembles plant Type-2 ribosome-inactivating proteins and bacterial botulinum toxins. The protomer has therefore a novel AB toxin combination of a MACPF-like chain linked by disulfide bonds to a lectin-like chain, indicating a delivery system for the former. This was further supported by observing PcPV2 binding to glycocalix of enterocytes in vivo and in culture, and by its hemaggutinating, but not hemolytic activity, which suggested an interaction with surface oligosaccharides. PcPV2 is able to get into predator's body as evidenced in rats and mice by the presence of circulating antibodies in response to sublethal oral doses. To our knowledge, a lectin-pore-forming toxin has not been reported before, providing the first evidence of a neurotoxic lectin in animals, and a novel function for ancient and widely distributed proteins. The acquisition of this unique neurotoxic/antinutritive/storage protein may confer the eggs a survival advantage, opening new perspectives in the study of the evolution of animal defensive strategies.